2005
DOI: 10.1007/s10038-005-0302-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of histamine-N-methyltransferase (HNMT) polymorphisms with asthma in the Indian population

Abstract: Histamine plays a major role in allergic disorders, including asthma. A major pathway of histamine biotransformation in the lungs is mediated by histamine N-methyltransferase (HNMT). We investigated the association of a functional SNP C314T; a SNP A929G, a (CA) n repeat in intron 5, and a novel (CA) n repeat (BV677277), 7.5 kb downstream of the HNMT gene with asthma and its associated traits such as total serum IgE levels in a case-control as well as in a family-based study design. In contrast to a previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
(33 reference statements)
3
11
2
1
Order By: Relevance
“…Szczepankiewicz et al found that the TT genotype for HNMT 314 was more common in Caucasian children with asthma compared to those without the disease (28) . But these findings were not confirmed by other studies that evaluated the same SNP in relation to asthma in German, Japanese, Indian, or Spanish-Caucasian asthma subjects (21, 25-27) . Similarly, we did not identify an association between the variant and asthma among our cohort.…”
Section: Discussioncontrasting
confidence: 72%
“…Szczepankiewicz et al found that the TT genotype for HNMT 314 was more common in Caucasian children with asthma compared to those without the disease (28) . But these findings were not confirmed by other studies that evaluated the same SNP in relation to asthma in German, Japanese, Indian, or Spanish-Caucasian asthma subjects (21, 25-27) . Similarly, we did not identify an association between the variant and asthma among our cohort.…”
Section: Discussioncontrasting
confidence: 72%
“…Polymorphisms in the HDC and SLC22A3 genes influenced the risk of both rhinitis and asthma [19]. The association of asthma with HNMT SNP could not be observed in two Caucasian (Spanish and German) and an Indian population [20,21,22]. HNMT gene polymorphism did not influence the endophenotypes of asthma in the German group either [21].…”
Section: Discussionmentioning
confidence: 99%
“…Three other SNPs have also been investigated within the pathway which also result in differences in enzyme function (ABP1 47 C/T, ABP1 995 C/T, and ABP1 4107C/G). Although the functional significance of many identified SNPs within the pathway is unknown, several studies have been conducted to explore potential associations between histamine related genes and asthma and allergic disease which have yielded mixed results (5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, previous studies have often been conducted among undefined asthma phenotypes and typically only included SNPs within single genes.…”
Section: Introductionmentioning
confidence: 95%
“…Genetic variation has been observed among the genes coding for the proteins responsible for histamine production, response, and degradation (HDC, HRH1, HRH2, HRH3, HRH4, HNMT, ABP1) (5). For example, one singlenucleotide polymorphism (SNP), HNMT314 C/T has been widely investigated in relation to asthma and allergic disease (16)(17)(18)(19)(20)(21). This polymorphism results in an amino acid change (Ala138Val) and decreased enzyme activity (22).…”
Section: Introductionmentioning
confidence: 98%